The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jafc.0c04425
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Bioavailability, Biotransformation, and Excretion of Nobiletin in Lean and Obese Rats

Abstract: Nobiletin, one of the prevalent polymethoxyflavones in citrus peels, was reported to possess various health benefits. We conducted the excretion study and pharmacokinetics study of nobiletin via oral administration and intravenous injection and 15 day consecutive dosing study using the high fat diet-induced obese rats and their lean counterparts. By comparing the demethylated metabolite profiles in the urine and feces, gut microbiota demonstrated greater biotransformation activity on nobiletin than the host. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
3
23
1
Order By: Relevance
“…However, the excretion of Sin in feces conversely showed a significantly higher amount, which is possibly due to the undissolved Sin in corn oil. Based on our present result, it is intriguing to discover that, in general, Sin and its metabolites had higher urinary-to-fecal excretion ratios than nobiletin and its metabolites as previously reported, 18 although Sin contrarily possessed a weaker lipophilic property. While it was also indicated before that the double-sword effect of high lipophilicity on the one hand enhances the membrane permeability of compounds by facilitating their transcellular transport, on the other hand, it aggravates the metabolic clearance and consequently the first-pass metabolism.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…However, the excretion of Sin in feces conversely showed a significantly higher amount, which is possibly due to the undissolved Sin in corn oil. Based on our present result, it is intriguing to discover that, in general, Sin and its metabolites had higher urinary-to-fecal excretion ratios than nobiletin and its metabolites as previously reported, 18 although Sin contrarily possessed a weaker lipophilic property. While it was also indicated before that the double-sword effect of high lipophilicity on the one hand enhances the membrane permeability of compounds by facilitating their transcellular transport, on the other hand, it aggravates the metabolic clearance and consequently the first-pass metabolism.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…has been reported. 37 A subsequent study by Zhang et al further showed that the gut microbiota showed stronger biotransformation activity of nobiletin than the host, 38 indicating that the gut microbiota might be another important factor diminishing the absorption of OH-PMFs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Evidence is mounting that the gut microbiota is essential for PMF metabolism and PMFs can shape the microorganism characteristics. Modification of PMFs might be carried out by gut microorganisms, including demethylation, hydroxylation, glycosylation and ring opening [ 35 ]. Meanwhile, PMFs could influence metabolic pathways, for example, the amino acid metabolism pathway.…”
Section: Discussionmentioning
confidence: 99%